Antibiotics and healthcare facility-associated Clostridioides difficile infection: systematic review and meta-analysis 2020 update. (31st March 2021) - Slimings, Claudia; Riley, Thomas V
Abstract: Background: Antibiotic use is the most important modifiable risk factor for healthcare facility-associated Clostridioides difficile infection (HCFA-CDI). Previous systematic reviews cover studies published until 31 December 2012. Objectives: To update the evidence for associations between antibiotic classes and HCFA-CDI to 31 December 2020. Methods: PubMed, Scopus, Web of Science Core Collection, WorldCat and Proquest Dissertations & Theses were searched for studies published since 1 January 2013. Eligible studies were those conducted among adult hospital inpatients, measured exposure to individual antibiotics or antibiotic classes, included a comparison group and measured the occurrence of HCFA-CDI as an outcome. The Newcastle–Ottawa Scale was used to appraise study quality. To assess the association between each antibiotic class and HCFA-CDI, a pooled random-effects meta-analysis was undertaken. Meta-regression and subgroup analysis was used to investigate study characteristics identified a priori as potential sources of heterogeneity. Results: Carbapenems and third- and fourth-generation cephalosporin antibiotics remain the most strongly associated with HCFA-CDI, with cases more than twice as likely to have recent exposure to these antibiotics prior to developing HCFA-CDI. Modest associations were observed for fluoroquinolones, clindamycin and β-lactamase inhibitor combination penicillin antibiotics. Individual study effect sizes were variable and heterogeneity was observed for most antibiotic classes. Conclusions: This review provides the most up-to-date synthesis of evidence in relation to the risk of HCFA-CDI associated with exposure to specific antibiotic classes. Studies were predominantly conducted in North America or Europe and more studies outside of these settings are needed.